Effect of magnetic thermal vibration therapy combined with Femoston on endometrial repair in postoperative patients with moderate to severe intrauterine adhesions: a randomized controlled trial - Aiping Wu; Qun Huang; Jing Zhang; Liping Chen (Frontiers in Endocrinology, 2026)
Background Moderate to severe intrauterine adhesions (IUA) remain clinically challenging after hysteroscopic adhesiolysis because endometrial repair may be incomplete, and uterine perfusion may remain suboptimal. This study evaluated whether magnetic thermal vibration therapy (MTVT) combined with Femoston improves postoperative recovery compared with Femoston alone. Methods This single-center, parallel-group, randomized controlled superiority trial enrolled 200 postoperative women aged 18–40 years with moderate to severe IUA. Participants were randomized 1:1 to receive Femoston alone (control group) or MTVT plus Femoston (intervention group). The primary outcome was the change in endometrial thickness at 1 month. Secondary outcomes included duration of menstrual bleeding, menstrual blood loss assessed by the Pictorial Blood Loss Assessment Chart (PBAC), Doppler-derived perfusion indices, GQOLI-74 quality-of-life domains, and adverse events. Outcomes were assessed before treatment and 1 month after completion of therapy. Complete-case analysis included 191 participants (control, n=96; intervention, n=95). Results Both groups improved after treatment, but the intervention group showed significantly greater improvement in endometrial thickness and uterine perfusion-related parameters. Endometrial thickness increased from 4.7 ± 2.2 to 9.4 ± 3.1 mm in the intervention group versus 4.2 ± 1.9 to 7.9 ± 2.3 mm in the control group (P = 0.013). PBAC scores improved more in the intervention group (30.0 ± 15.3 to 80.7 ± 24.0 vs 31.1 ± 13.8 to 63.8 ± 20.3; P<0.001). Flow index (FI), vascularization index (VI), and vascularization flow index (VFI) increased significantly more, whereas pulsatility index (PI) and resistance index (RI) decreased significantly more, in the intervention group (all P<0.001). Psychological, physical, and social function scores also improved significantly more with the combined regimen, while duration of menstrual bleeding and material-life scores did not differ significantly between groups. Adverse events were uncommon and comparable (9/95 vs 11/96; P = 0.813), and no serious adverse events occurred. Conclusion MTVT combined with Femoston may provide greater short-term improvement in endometrial thickness, Doppler-derived perfusion indices, PBAC score, and selected quality-of-life domains compared with Femoston alone in postoperative women with moderate to severe IUA, without an apparent increase in adverse events. However, because this single-center trial primarily assessed short-term surrogate and symptom-based outcomes, larger multicenter studies with longer follow-up and hysteroscopic and reproductive endpoints are needed.